Native American Studies - Kidwell, Clara Sue (Introducing Ethnic Studies : IES, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748618613);This guide to Native American history and culture outlines new ways of understanding American Indian cultures in contemporary contexts.The book covers the key issues of:The intimate relationship of culture to land. The nature of cultural contact and conflict in the period after European contact. The unique relationship that Native communities have with the United States government.The significance of language.The vitality of contemporary cultures and the variety of artistic styles, from literature and poetry to painting and sculpture to performance arts.This thematic approach places history, culture and intellectual production in the contexts of politics and power. Using specific examples throughout, the culture of Native Americans is seen from the point of views of Native people as well as from the points of view of Europe and the United States.Key FeaturesNew approach to the subject.Argument shaped by interaction with Native scholars and members of Native communities.Draws on work of historians, anthropologists, ethnographers, literary critics and art historians.Literature survey with assessment of sources and detailed bibliography.Includes 18 colour plates.